Clinical And Radiological Evaluation of Effectiveness Comprehensive Treatment Generalized Periodontitis - Burxonova Zarafruz Qobilovna; Yuldasheva Durdona; Rahmonova Nigina; Abdusalomova Malikabonu (Genius Publishing Group, 2024)
In the complex treatment of generalized periodontitis, special attention is paid to the correct combination of conservative and surgical treatment methods that reduce the activity of destructive processes in periodontal tissues and restore lost anatomy [1-9]. However, despite various additions and modifications, conservative and surgical intervention on the periodontal itself does not create sufficient conditions for effective relief of pathological processes and restoration of periodontal tissues [10-18]. In some cases, the use of new technologies, including occupational hygiene, the use of dental splints and other conservative methods of treatment, does not lead to stabilization of destructive processes in the alveolar process, and in some cases contributes to further destruction of periodontal tissues and surrounding bone tissue with the formation of defects of various sizes. The problem of dental preservation in patients with generalized periodontitis of II-III severity is still relevant. The organizational inconsistency of dentists of different specialties, the absence of an actual medical examination of patients with periodontal disease create prerequisites for the interruption of treatment at the level of conservative therapeutic agents and the active course of destruction of bone tissue of the alveolar processes
Keywords: Generalized periodontitis; new technologies